Penerapan Strategi Multiple Intelligences pada Mata Pelajaran Pendidikan Agama Islam (Studi Kasus di SMP Negeri 3 Sungailiat) - Habibah, Habibah (PASCASARJANA IAIN SYAIKH ABDURRAHMAN SIDDIK BANGKA BELITUNG, 2019)
The success of the students are determined by the teacher who can guide them in learning and mastering the certain competencies. The psychological aspects show the fact that students generally have defferent levels of development, which also dmand different materi, everyone has deifferent ablities and talents. This study aims to find out how the aplication of Multiple Intelligences Strategies work in the sbujects of islamic education in SMP Negeri 3 Sungailiat and its influence on student learning education. The result of the study showed that by applying the Multiple Intelligences strategy in the subjects of islamic education proved that the level of student activity had been increased. There are also an obstacles in aplication of learning strategies multiple intellegencesa : learning prepartion, implementation of learning and assessment. Therefore, lectures sued to more creative in improving intellignces of students.